A Study of Folk Lanna Music Instruction for Elderly: A Case Study of Kru Prommate Sabpasri (Traditional Thai Northern Folk Music Teacher) - สรรพศรี เพียงแพน; ฉัพพรรณรัตน์ ยุทธนา (Journal of Fine and Applied Arts Khon Kaen University, 2019)
The purpose of this research is to study the identity of teaching Thai northern folk music for the elder of Kru Prommate Sabpasri (Traditional Thai northern folk music teacher) by using the qualitative research method. The information are gathered by emphasizing on interview with a observation. The result of the research found that using Andragogy, a thinking framework, as a base, which is a theory for elder invented by Knowles (1980). The display identity of teaching the elder can be seen as below: 1) Making a comfortable, friendly, and acceptance atmosphere, as well as respect to each other between instructor and students, and within the students. 2) Planning and organize the structure together between instructor and the elders, and assign separated role to each member of elders. 3) Analyze the requirement together between the instructor and the elders. There are discussions about the requirement of the students all the time. 4) Specify the objective of learning and prioritize the happiness of playing Thai northern folk music. 5) Design the learning experience about the rhythmic, fundamental of musical instrument, reading musical notes, group training, and showing off. 6) The learning activity, which prioritize the group playing of Sa-lor together and 7) Evaluate the result of learning by observation the performance of playing music in any volunteered occasion. There are also have the integration between the instructor and the students.